Duodenal intramural abseye bağlı mide çıkış obstrüksiyonu: Olgu sunumu - (:unkn) unknown (My University, 1997)
0

Gastric Outlet Obstruction Secondary to Duodenal Intra¬mural, Abscess Complicating Intramural Hematoma Gastric outlet obstruction may exist as an emergency situ¬ation with a high morbidity and mortality. Peptic ulcus disease of pylorus and duodenum, tumors of pancreas and duodenum and duodenal intramural hematoma are the possible etiological factors of this clinic entity. Here, we report a case study of duodenal intramural ab¬scess as a cause of gastric outlet obstruction. The presen¬tation and the surgical therapy of this unique entity is dis¬cussed.
Gastric outlet obstruction secondary to duodenal intramural abscess complicating intramural hematoma
Keywords: Cerrahi